AC ionic conductivity and DC polarization method of lithium ion transport in PMMA-LiBF 4 gel polymer electrolytes - Osman, Z.; Mohd Ghazali, M.I.; Othman, L.; Md Isa, K.B. (Elsevier, 2012)
Polymethylmethacrylate (PMMA)-based gel polymer electrolytes comprising ethylene carbonate-propylene carbonate (EC/PC) mixed solvent plasticizer and various concentrations of lithium tetrafluoroborate (LiBF 4) salt are prepared using a solvent casting technique. Electrical conductivity and transference number measurements were carried out to investigate conductivity and charge transport in the gel polymer electrolytes. The conductivity results show that the ionic conductivity of the samples increases when the amount of salt is increased, however decreases after reaching the optimum value. This result is consistent with the transference number measurements. The conductivity-frequency dependence plots show two distinct regions; i.e. at lower frequencies the conductivity increases with increasing frequency and the frequency independent plateau region at higher frequencies. The temperature-dependence conductivity of the films seems to obey the Arrhenius rule. Â© 2012 Elsevier B.V.